Development and benefits of MDevSPICE®, the medical device software process assessment framework. Issue 9 (1st April 2016) - Lepmets, Marion; McCaffery, Fergal; Clarke, Paul
Abstract: Software development companies moving into the medical device domain often find themselves overwhelmed by the number of regulatory requirements they need to satisfy before they can market their device. Several international standards and guidance documents have been developed to help companies on their road to regulatory compliance, but working their way through the various standards is a challenge in itself. In order to help software companies in the medical device domain, we have developed an integrated framework of medical device software development best practices called MDevSPICE®. This framework integrates generic software development best practices with medical device standards' requirements enabling consistent assessment of medical device processes. MDevSPICE® can be used by software companies evaluating their readiness for regulatory audits as well as by large medical device manufacturers for selecting suitable software suppliers. In this paper, we describe the development of the MDevSPICE® framework—its process reference model, process assessment model, assessment method and assessor training and certification scheme. We also illustrate the benefits and significance of the framework for the medical device‐manufacturing community as learned from the various MDevSPICE® assessments that we conducted to date. Copyright © 2016 John Wiley & Sons, Ltd.